2008
DOI: 10.1016/j.expneurol.2007.11.015
|View full text |Cite
|
Sign up to set email alerts
|

A ketogenic diet rescues the murine succinic semialdehyde dehydrogenase deficient phenotype

Abstract: Succinic semialdehyde dehydrogenase (SSADH) deficiency is an heritable disorder of GABA degradation characterized by ataxia, psychomotor retardation and seizures. To date, there is no effective treatment for SSADH deficiency. We tested the hypothesis that a ketogenic diet (KD) would improve outcome in an animal model of SSADH deficiency, the SSADH knockout mouse (Aldh5a1 −/− ). Using a 4:1 ratio of fat to combined carbohydrate and protein KD we set out to compare the general phenotype, in vivo and in vitro ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 57 publications
4
60
0
Order By: Relevance
“…The study of adult mutant mice was possible only after maintaining them exclusively on the KD from weaning day (P20) onward [9,10]. Aldh5a1 −/− pups that continue to suckle beyond P20 survive longer than their weaned mutant littermates (unpublished), suggesting that the high-fat dam's milk exerts a beneficial effect in this disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of adult mutant mice was possible only after maintaining them exclusively on the KD from weaning day (P20) onward [9,10]. Aldh5a1 −/− pups that continue to suckle beyond P20 survive longer than their weaned mutant littermates (unpublished), suggesting that the high-fat dam's milk exerts a beneficial effect in this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For wild-type (WT) mice, food and water were freely available throughout the study. Mutant mice were obtained from litters maintained exclusively on the KD [9,10] from weaning day onward. The rationale for using KD-treated animals is that absent this dietary treatment, no mutant animals survived to adulthood.…”
Section: Animal Husbandrymentioning
confidence: 99%
See 1 more Smart Citation
“…In hippocampal in vitro seizures models, KD feeding limited epileptic activity in several portions of the hippocampus by promoting ATP-sensitive K+ channel activity that is implicated in plasma membrane excitability and in regulation of aerobic metabolism [29][30][31]. Both augmentation of fast GABAergic (GABA A ) neurotransmission and decreased probability of excitatory neurotransmitter release from presynaptic neurons have been implicated in the anticonvulsivant actions of the KD [32,33]. In fact, elevated concentrations of KBs have been reported to increase and maintain synaptosomal GABA contents at a higher value [34] and increase the intracellular concentration [35] and cause presynaptic input reduction of glutamate [31].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that in Aldh5a1(-/-) mice KD restores hippocampal ATP levels (Nylen et al 2009) and significantly improves clinical phenotype (Nylen et al 2008). However, there are no reports of KD treatment of patients with SSADH deficiency.…”
Section: Adenylosuccinate Lyase (Adsl) Deficiencymentioning
confidence: 99%